Conceptualizing the Human Health Outcomes of Acting in Natural Environments: An Ecological Perspective - Brymer, Eric; Araújo, Duarte; Davids, Keith; Pepping, Gert-Jan (Frontiers in Psychology, 2020)
Human-nature interactions are important for wellbeing and health benefits. Research has shown that pictures of nature, interacting with nature, physical activity in nature, immersion in nature and feeling connected to nature can improve health. While considerable research supports this notion, theoretical and conceptual frameworks that help explain how the natural environment provides benefits to human health and wellbeing are limited. In extreme cases, theoretical approaches reinforce a problematic notion where nature is viewed as a separate entity, as a treatment to be taken as prescribed to remediate health problems that arise. Such approaches are limited as they fail to address how beneficial person-nature relations may be captured in interventions. There is a need for a deeper understanding of the processes underlying the observed benefits of the person-nature link in order to design effective research and interventions. It is especially important to consider the implications of research on person-nature relations for people living in urban contexts. In this paper, we present an ecological perspective building on James Gibson’s conceptualisation of human behaviour. Specifically, we outline a framework that emphasises the person-environment system as the most appropriate scale of analysis. We present three relevant concepts from the ecological approach: form of life, affordances and niche construction, as helpful for appreciating how acting in natural environments might benefit human health and wellbeing. This approach urges policy makers and urban designers to rethink environmental designs to provide and support a landscape of affordances that makes use of the richness of natural environments.